Antioxidant potential and in vitro inhibition of starch digestion of flavonoids from Crataegus pinnatifida. Issue 10 (October 2022) - Huang, Xin; Bian, Yuanyuan; Liu, Tianzhi; Xu, Zhuang; Song, Ziqi; Wang, Fei; Li, Tuoping; Li, Suhong
Abstract: Hawthorn flavonoids were extracted by enzymolysis associated ultrasonic procedure. Thirteen flavonoids were identified by HPLC/ESI-QTOF/MS, and the major components were procyanidin C1, rutin-rhamnoside, vitexin-rhamnoside, and catechin. Hawthorn flavonoids exhibited strong free radical scavenging activities against DPPH, ABTS, and hydroxyl radicals. Total and intercellular antioxidant experiments revealed that the free hydro-PSC value was 295.32 ± 12.20 μmol of VCE/g DW, and the free cellular antioxidant activity (CAA) values were 168.60 ± 4.87 μmol of QE/g DW in the no PBS wash protocol and 49.53 ± 1.75 μmol of QE/g DW in the PBS wash protocol. In addition, hawthorn flavonoids exhibited higher α-amylase and α-glucosidase inhibitory activities. The wheat starch digestibility was also reduced by hawthorn flavonoids as well. The results indicated that enzymolysis associated ultrasonic extraction was advisable for extracting flavonoids from hawthorn, and hawthorn flavonoids might be recommended as a potential food supplement with hypoglycemic activities. Abstract : Flavonoids; Antioxidant activity; α-Amylase; α-Glucosidase; Starch digestion. Highlights: Ultrasound-enzymolysis combination improved the extraction yield of hawthorn flavonoids. Procyanidin C1 and rutin-rhamnoside were major composition of hawthorn flavonoid. Hawthorn flavonoids possessed the significant effects on antioxidation and anti-α-amylase, α-glucosidase. Hawthorn flavonoids reduced the digestion rate of wheat starch.